Variations on the theme: focus on cerebellum and emotional processing - Ciapponi, Camilla; Li, Yuhe; Osorio Becerra, Dianela A.; Rodarie, Dimitri; Casellato, Claudia; Mapelli, Lisa; D’Angelo, Egidio (Frontiers in Systems Neuroscience, 2023)
The cerebellum operates exploiting a complex modular organization and a unified computational algorithm adapted to different behavioral contexts. Recent observations suggest that the cerebellum is involved not just in motor but also in emotional and cognitive processing. It is therefore critical to identify the specific regional connectivity and microcircuit properties of the emotional cerebellum. Recent studies are highlighting the differential regional localization of genes, molecules, and synaptic mechanisms and microcircuit wiring. However, the impact of these regional differences is not fully understood and will require experimental investigation and computational modelling. This review focuses on the cellular and circuit underpinnings of the cerebellar role in emotion. And since emotion involves an integration of cognitive, somatomotor, and autonomic activity, we elaborate on the tradeoff between segregation and distribution of these three main functions in the cerebellum.